An efficient QOS routing protocol for mobile ad-hoc networks - Joe, Inwhee (2006)
To satisfy the user requirements for continuous and real-time multimedia information, the concept of Quality of Service (QoS) has emerged as a main issue in mobile ad-hoc networks. QoS routing is to find a route according to the QoS requirements of the users. In this paper, we propose an efficient QoS routing protocol that is based on AODV over TDMA, one of the typical routing protocols for mobile ad-hoc networks, by making a bandwidth reservation for QoS guarantee. While the existing schemes calculate the maximum available bandwidth for each candidate path, our scheme is to check only if the bandwidth of a given path satisfies the end-to-end QoS requirement. Also, the key idea in the bandwidth reservation is to select carefully time slots without causing any conficts in the wireless environment, thereby maximizing the bandwidth efficiency. In order to evaluate the performance of the proposed QoS routing protocol, some simulations are carried out in the adhoc environment. The simulation results show that the proposed protocol provides sufficiently low and stable delay performance regardless of the offered load.